2020
DOI: 10.4103/tcmj.tcmj_127_19
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the doula program in Northern Taiwan

Abstract: Objective: The cesarean section rate in Taiwan is 32%–34%, exceeding the rate that the World Health Organization considers reasonable. A doula is a trained woman who provides physical, emotional, and informational support to pregnant women before, during, and after delivery. This study investigated the effectiveness of a new doula program in Northern Taiwan. Materials and Methods: A quasi-experimental research design was employed. Two hundred and twenty women, divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Maternal satisfaction includes all dimensions of care including: physical environment, cleanliness, availability of resources, interpersonal behavior, privacy, promptness, cognitive care, perceived provider competency, and emotional supports [ 49 ]. Similar to the present study, in some studies, the presence of doula as a lay companion increases maternal satisfaction with the experience of childbirth [ 14 , 28 , 50 , 51 ]. Providing continuous doula program to pregnant women produces highest level of satisfaction [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Maternal satisfaction includes all dimensions of care including: physical environment, cleanliness, availability of resources, interpersonal behavior, privacy, promptness, cognitive care, perceived provider competency, and emotional supports [ 49 ]. Similar to the present study, in some studies, the presence of doula as a lay companion increases maternal satisfaction with the experience of childbirth [ 14 , 28 , 50 , 51 ]. Providing continuous doula program to pregnant women produces highest level of satisfaction [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Providing continued support for the expectant mother and correct and appropriate information during labor and delivery result in the mother's comfort and tranquility and help her to identify the source of pain correctly and consider childbirth as a positive life event [6]. Several studies showed that mothers supported by doulas were happier and more satisfied with their childbirth experience [7][8][9].…”
Section: Introductionmentioning
confidence: 99%